Preliminary evaluation of a novel non-linear frequency compression scheme for use in children. (2nd December 2017) - Wolfe, Jace; Duke, Mila; Schafer, Erin C.; Rehmann, Julia; Jha, Siddhartha; Allegro Baumann, Silvia; John, Andrew; Jones, Christine
Abstract: Objective : The primary goal of this study was to evaluate a new form of non-linear frequency compression (NLFC) in children. The new NLFC processing scheme is adaptive and potentially allows for a better preservation of the spectral characteristics of the input sounds when compared to conventional NLFC processing. Design : A repeated-measures design was utilised to compare the speech perception of the participants with two configurations of the new adaptive NLFC processing to their performance with the existing NLFC. The outcome measures included the University of Western Ontario Plurals test, the Consonant-Nucleus-Consonant word recognition test, and the Phonak Phoneme Perception test. Study sample : Study participants included 14 children, aged 6–17 years, with mild-to-severe low-frequency hearing loss and severe-to-profound high-frequency hearing loss. Results : The results indicated that the use of the new adaptive NLFC processing resulted in significantly better average word recognition and plural detection relative to the conventional NLFC processing. Conclusion : Overall, the adaptive NLFC processing evaluated in this study has the potential to significantly improve speech perception relative to conventional NLFC processing.